Serotoninergic Modulation of Phototactic Variability Underpins a Bet-Hedging Strategy in Drosophila melanogaster - Krams, Indrikis A.; Krama, Tatjana; Krams, Ronalds; Trakimas, Giedrius; Popovs, Sergejs; Jõers, Priit; Munkevics, Maris; Elferts, Didzis; Rantala, Markus J.; Makņa, Jānis; de Bivort, Benjamin L. (Frontiers in Behavioral Neuroscience, 2021)
When organisms’ environmental conditions vary unpredictably in time, it can be advantageous for individuals to hedge their phenotypic bets. It has been shown that a bet-hedging strategy possibly underlies the high inter-individual diversity of phototactic choice in Drosophila melanogaster. This study shows that fruit flies from a population living in a boreal and relatively unpredictable climate have more variable variable phototactic biases than fruit flies from a more stable tropical climate, consistent with bet-hedging theory. We experimentally show that phototactic variability of D. melanogaster is regulated by the neurotransmitter serotonin (5-HT), which acts as a suppressor of the variability of phototactic choices. When fed 5-HT precursor, boreal flies exhibited lower variability, and they were insensitive to 5-HT inhibitor. The opposite pattern was seen in the tropical flies. Thus, the reduction of 5-HT in fruit flies’ brains may be the mechanistic basis of an adaptive bet-hedging strategy in a less predictable boreal climate.